2019
DOI: 10.1111/dme.14109
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent diabetic ketoacidosis and a brief history of brittle diabetes research: contemporary and past evidence in diabetic ketoacidosis research including mortality, mental health and prevention

Abstract: Pharmacological, technological and educational approaches have advanced the treatment of Type 1 diabetes in the last four decades and yet diabetic ketoacidosis (DKA) continues to be a leading cause of admission in Type 1 diabetes. This article begins by reviewing the contemporary epidemiological evidence in DKA. It highlights a rise in DKA episodes in the last two decades, with DKA continuing to be the leading cause of death in young people with Type 1 diabetes, and that DKA episodes are a marker for subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Whether this is ketosis-prone T2DM is unknown, as genetic analyses on these individuals are unavailable. Psychological factors also influence the likelihood of developing DKA 55,56 . A report of ~350 adolescent girls and women (aged 13-60 years) suggested that disordered eating was a contributing factor in ~20% of recurrent episodes of DKA 57 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Whether this is ketosis-prone T2DM is unknown, as genetic analyses on these individuals are unavailable. Psychological factors also influence the likelihood of developing DKA 55,56 . A report of ~350 adolescent girls and women (aged 13-60 years) suggested that disordered eating was a contributing factor in ~20% of recurrent episodes of DKA 57 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Whereas the outcome of DKA has improved tremendously over the last decades, 4,30 the incidence remained stable, and recurring events or readmission to a hospital are frequent concerns 15,18,22‐24,31 . Previous studies of repetitive DKA events were designed as case–control‐studies, 30 analyzed only a group of patients with DKA‐related hospital admissions, covered a shorter period of time 18,19,24 or a smaller group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a sensitivity analysis performed by us, the GISD_2012 was used to adjust models for regional deprivation, with similar results: a previous episode of DKA remained a significant risk factor for recurrence, underlining that patients with previous episodes should be followed closely. Targeted patient education may also help to reduce recurrence risk: structured patient education or multidisciplinary support programs can improve glycemic control 34 and reduce hospital admissions for DKA 22,35 . A language barrier is associated with higher HbA1c levels 36 and may partly explain the higher risk for DKA in patients with a migratory background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigs showed symptoms consistent with the brittle type of diabetes. 43 CSII may offer an alternative therapeutic strategy in this case. 28 However, the CSII pump was too heavy for use in neonatal pigs, and the use of the CSII pump attached to the piglets' cage (with the insertion of an insulin injection needle using a long tube) was also ineffective because the tubes became clogged, and the needles were detached.…”
Section: Pdx1-hes1mentioning
confidence: 94%